Common Psychological and Behavioral Disorders in Transgender People: An Epidemiological Review - Mohammad-Rafi Bazrafshan; Ahmadreza Eidi; Omid Soufi; Hamed Delam (Shiraz University of Medical Sciences, 2021)
Background: In the last two decades, the number of people who have referred to mental health services due to concerns about gender identity has increased dramatically. The aim of this study was to present the most important and fundamental results of studies on transgender psychological and behavioral disordersand compare these results. Methods: This is a narrative review study. Search for articles related to common psychological and behavioral disorders in transgender people was done by two trained researchers between December 2019 and March 2020 in 5 Latin scientific databases (Google Scholar, PubMed / Medline, Scopus, ISI Web of Science and Embase). Results: Psychological and behavioral disorders were much higher in transgender people than in the general population. The most common disorders included anxiety and depression, suicidal attempt, drug abuse, self-injury without suicidal tendency, and HIV. Conclusion: Transgender people are constantly harassed and abused by friends, acquaintances, classmates and teachers, and even their families. Having multiple sexual partners increases the risk of HIV infection and other sexual misconduct. Therefore, governments need to implement their support programs through training centers and counseling for transgender individuals.